2020
DOI: 10.1111/1556-4029.14581
|View full text |Cite
|
Sign up to set email alerts
|

Application of forward‐looking infrared (FLIR) imaging from an unmanned aerial platform in the search for decomposing remains

Abstract: Police officers are often required to search geographically varied and large areas for human remains during the early stages of death investigations; including, misadventure, homicide, and mass casualties (e.g., terrorism, natural disasters). In many jurisdictions, current practice for searching large, open areas is by physical inspection by personnel, dogs trained to detect the scent of human decomposition (="cadaver dogs"), and aerial search using manned helicopters. Such methods have limitations, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
(37 reference statements)
4
15
0
Order By: Relevance
“…In line with previously published literature [5, 8, 20], a distinguishable surface temperature difference between the control and experimental graves was detected when analyzing the findings of the research area. The total weight of the buried carcasses and the grave depth of the present study were almost the same as those in previously reported experiments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with previously published literature [5, 8, 20], a distinguishable surface temperature difference between the control and experimental graves was detected when analyzing the findings of the research area. The total weight of the buried carcasses and the grave depth of the present study were almost the same as those in previously reported experiments.…”
Section: Discussionsupporting
confidence: 89%
“…The advantage of remote sensing deployed using drone technology lies in its non-invasive nature that covers a large area of interest in a short amount of time with minimal human and non-human resources [4]. In forensic science, remote sensing has been used in various cases to aid criminal investigation [4][5][6][7][8][9]. Past research has demonstrated that optical remote sensing can detect burial sites in tropical forests [1], rural landscapes [10], mountainous terrain [11], and woodland [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent research [2,[32][33][34][35][36][37][38][39] has underlined the usefulness of UAVs as a forensic detection tool or as a source of high-quality data for the documentation and reconstruction of the forensic scene. The existing literature focuses mainly on the application of UAV-based aerial photography for the detection of clandestine burials in the field of forensic archeology [33,34,37,40] or for documentation purposes in crime scene or accident investigations [32,35,36,38,39]. Going one step further, Rocke et al [41] added a Geoforensic Search Strategy (GSS) perspective to the drone deployment in the context of assessing the likelihood of detecting a buried target based on the observation of general ground conditions using technological advances in remotely sensed aerial imagery.…”
Section: Literature Review Summarymentioning
confidence: 99%
“…In a 2020 study by Butters et.al., an infrared sensor was mounted to a DJI drone and flown over a simulated burial using two large cuts of pork. The infrared sensor imaged a thermal anomaly as decomposition from insect activity progressed [14]. Remote sensing such as this and drone-mounted LiDAR [15] are relatively new to crime scene detection and are not within the scope of this study.…”
Section: Highlightsmentioning
confidence: 99%